Optimal muscle training - Kinakin, Ken 1962- (Human Kinetics, 2008)
This essential training book presents a complete program for optimizing strength, increasing growth, and minimizing injury. And with its multiple menus, the DVD allows you to customize your experience by quickly accessing what is most relevant to your needs. Overall, the "Optimal Muscle Training" book and DVD is a powerful training package